Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Makanan dan Minuman Tbk - Vina Arnita; Nina Andriany Nasution; Murnihati Murnihati (Mahesa Research Center, 2021)
The research aims to analyze the influence of the investment opportunity set, profitability and operating leverage on the capital structureof food and beverage companies listed on the Indonesian Stock Exchange for the 2014-2018 period. Determination of samples using purposive sampling with criteria namely food and beverage companies listed on the Indonesian Stock Exchange and those who publish financial statements in a row during the 2014-2018 period, obtained 10 companies that meet the criteria and 5 years of observation to produce 50 samples. The results of the study indicate that the investment opportunity set variable in a negative and not significant effect on capital structure with a significance value of 0,129> 0,05, profitability in a positive and significant effect on capital structure with a significane value of 0,031< 0,05 and operating laverage in a prsial positive and significant effect on capital structure with a significance value of 0,030< 0,05. Investment opportunity set, profitability and operating laverage simultaneously influence the capital structure with a significance value of 0,049 > 0,05. Investment opportunity set, profitability and operating laverage are able to explain the capital structure of 10,5% is expalined by other factors not included in this study.